Ensino de Português como língua adicional para refugiados venezuelanos mediado por uma abordagem de ensino intercultural - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The teaching of Brazilian Portuguese has expanded in Brazil over the years because of the increase of refugees/immigrants recognized in the country in the late 2020s. Therefore, the Federal Universities have started to promote more courses in Portuguese as an Additional Language, PLA, aimed at this public, refugees/immigrants, with the purpose of contributing to the integration process of these foreigners where they are inserted. It is in these pedagogical spaces created by Universities that the teaching of PLA is able to promote the welcoming of refugee/immigrant students by trying to integrate them through a didactic-intercultural mediation between different cultural subjects-worlds. In this regard, we see the importance of developing didactic materials that contain culturally sensitive contents and approaches for teaching and learning PLA in the search for knowledge that are mediated by intercultural dialogues in order to contribute with the teaching and learning process of these students. In addition, to consider also in the elaboration of these materials issues related to cultural Identities, focused on our "belonging", in relation to our conceptions of identity, of being part of a specific group, social, political or religious. The aim of this research was to investigate how the integration of refugee/immigrant students happened through interculturality and welcoming in Portuguese as an Additional Language (PLA) classes taught in the course "Aspects of Brazilian Culture" to a Venezuelan family. For this, it was made a descriptive analysis of the elaboration of the lesson plans of the module "Identities" and an analysis of the reports made in the class by the students through the recordings. From the data analysis, it was possible to identify the intercultural dialogues that were promoted in the lesson plans and some challenges related to the teaching of Portuguese as a Host Language on an intercultural perspective.
Keywords: Português como Língua Adicional; Acolhimento; Interculturalidade; Portuguese as an Additional Language; Welcoming; Interculturality; CNPQ::LINGUISTICA, LETRAS E ARTES